CT raw data (DICOM format) of sediment core GeoB18116-2 from Dragon Mound, Alborán Sea, Maria S. Merian cruise MSM36 - Greiffenhagen, Luis; Titschack, Jürgen; Wienberg, Claudia; Wang, Haozhuang; Hebbeln, Dierk; Timann, Christian; Lemke, Arne-Jörn (PANGAEA, 2025)
Archive halves of core GeoB18116-2 were scanned using a Philips computer tomography (CT) Brilliance iCT Elite 256 at the hospital Klinikum Bremen-Mitte, Bremen, Germany, with an X-ray source voltage of 120 kV and a current of 300 mA at a resolution of 0.293 mm in the x and y directions and 0.625 mm resolution in the z-direction (0.3 mm reconstruction interval). Images were reconstructed using the filtered Back Projection (fBP) mode and a bone kernel (YB (Enhanced)).
Keywords: Alboran Sea; Cold-water coral; cold-water coral mound; cold-water coral mound formation; Continental Slope; CT scan; MeBo